2020
DOI: 10.1039/c9cp05934b
|View full text |Cite
|
Sign up to set email alerts
|

Understanding 125Te NMR chemical shifts in disymmetric organo-telluride compounds from natural chemical shift analysis

Abstract: Magnetic coupling of the lone pair: theoretical investigations reveal the origin of 125Te chemical shift in disymmetric organotellurides

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 59 publications
1
23
0
Order By: Relevance
“…Furthermore, each chemical shi component can be further assigned to contribution of individual localized orbitals via natural localized molecular orbital (NLMO) analysis. This method has been applied to various nuclei ( 13 C, 15 N, 17 O, 27 Al, 77 Se, 125 Te, 195 Pt etc.) to provide understanding of NMR parameters on a molecular level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, each chemical shi component can be further assigned to contribution of individual localized orbitals via natural localized molecular orbital (NLMO) analysis. This method has been applied to various nuclei ( 13 C, 15 N, 17 O, 27 Al, 77 Se, 125 Te, 195 Pt etc.) to provide understanding of NMR parameters on a molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…to provide understanding of NMR parameters on a molecular level. [18][19][20][21][22][23][24][25][26][27] Herein we show by DFT calculations using a series of distinct molecular Y(III) complexes, the underlying factors for their chemical shi signature in dependence on the ligands and coordination number.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, all the considered tellurium compounds were synthesized and characterized by the 125 Te NMR spectroscopy, in a series of papers [408][409][410] including the one under consideration. [405] The linear regression fit, obtained in Pietrasiak et al [405] for 14 points, confirmed that 125 Te NMR chemical shifts can be reproduced by ZORA DFT calculations with a reasonable accuracy. Meticulous NCS analysis, performed in Pietrasiak et al, [405] revealed that, in general, the 125 Te chemical shielding constants of molecules of general structure A are mostly determined by the magnetically induced coupling of a p-character tellurium lone pair and Te-ligand antibonding orbitals.…”
mentioning
confidence: 61%
“…Both optimized structures were used to calculate the The ZORA NMR calculations have been performed by Pietrasiak et al [405] within the GIAO-PBE0 framework using Slater-type basis sets of quadruple-and triple-ζ quality for tellurium and the other atoms, respectively.…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation